Institutional Ethnography of Women Faculty in Higher Education: Understanding Gendered Experiences and Power Dynamics (Higher Education Politics and Economics, 2025)
In this study, we explored the day-to-day work of women faculty members in higher education to understand the impact of various processes, policies, procedures, and discourses on their work-life balance. Utilizing feminist standpoint theory, we analyzed data collected from four focus groups to highlight the challenges and barriers women faculty encounter in balancing their professional and personal lives, with a particular focus on how privilege and power dynamics influence their academic experiences. Framed as an institutional ethnography, our analysis reveals that women faculty often struggle to balance their personal and professional responsibilities. Participants described the challenges of rigid work schedules, insufficient medical leave, and heavy and uneven workloads. These findings reinforced the need for equitable policies to create a more inclusive and empowering academic environment for women faculty members.